(untitled) - Kanuk, Alan R. (Hoboken, N.J, 2007)
Capital Markets in India: An Investor's Guide aims to provide the first comprehensive book on investing in the India markets. India is right now at the forefront of globalization. The book's focus is on the equity market, but it also addresses derivatives, fixed income, and foreign direct investments. Chapter topics include facts about the Indian economy; the Foreign Institutional Investor (FII) regulations, registration process, and applications; detail about the market regulation and the regulator; the very important market safeguards built into the Indian market systems; and lists of companies ranked by various criteria such as capitalization, turnover, industry, and earnings. The book even supplies investors and traders with contact information for many of the key institutions and market players. Readers will not only gain basic information about how the markets in India work, but also the contacts and facts to help them with their own investing plan.
Keywords: Capital market,Stock exchanges,Thị trường vốn,Sở giao dịch chứng khoán; India,India,Ấn Độ,Ấn Độ